Efektifitas Animated Video Berbasis Theory Of Planned Behaviour dalam Meningkatkan Kepatuhan Pengetahuan Perawatan Kaki pada Pasien Diabetes Melitus - Muhammad Anis Taslim; Bagus Ananta Tanujiarso; Akub Selvia; Muhammad Dwi Kurniawan (Universitas Muhamadiyah Manado, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by persistently high blood sugar levels, which can lead to complications such as diabetic foot issues. A crucial aspect for healthcare professionals providing care to DM patients is assessing the patient's level of adherence and understanding regarding self-care and disease management. Data from the 2023 SKI (Indonesian Health Survey) indicates there were 118,184 cases of Diabetes Mellitus in Central Java. Foot care education delivered via remote services assists patients in performing proper foot care to prevent complications associated with the condition. This study aimed to determine the effectiveness of an animated video based on the Theory of Planned Behavior in improving the knowledge and adherence of patients with diabetic ulcers. A quasi-experimental design was employed, utilizing a one-group pre-test and post-test approach with a control group. Incidental sampling was used to select 60 respondents. The Mann-Whitney test yielded a p-value of < 0.05 (0.017), demonstrating that the animated video based on the Theory of Planned Behavior was effective in enhancing both adherence and knowledge among patients with diabetic ulcers. The findings suggest that this animated video, leveraging audiovisual media, can be implemented in educational settings to help prevent foot complications in patients with diabetes.